Pengalaman Pemandu Perjalanan Wisata Perempuan dalam Struktur Gender yang Berlapis - Irma Sania Putri (Gadjah Mada Journal of Tourism Studies, 2026)
The tourism industry employs a large number of workers, including tour guides who play an important role in shaping the tourist experience. However, this profession is generally carried out in a freelance work system characterized by job uncertainty and a lack of formal protection. For women, these conditions intersect with gender norms and unequal domestic responsibilities, creating a complex and layered work experience. This study aims to analyse the work experiences of female tour guides through the lens of gender as a social structure and intersectionality, with the characteristics of the tour guiding profession and the freelance work system positioned as the social and structural context that frames these experiences. This study employs a qualitative approach using in-depth interviews, non-participant observation, and documentation of seven female tour guides. Data analysis was conducted using thematic analysis. Findings show that work experiences of female tour guides are shaped by gender, which operates in multiple layers at the individual, relational, and institutional levels. These findings confirm that such experiences are not purely individual but rather the result of interactions between gender identity, social relations, and institutional structures within the labour system. Theoretically, this study emphasizes the importance of viewing the labour market and job characteristics as factors that shape women’s work experiences, while also expanding the application of the gender framework as a structural lens through the integration of an intersectional perspective.